CTA Annual Report 2011: A year of renewal - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2012)
For CTA, 2011 was a year of renewal. Following the approval of the 2011–2015 strategic plan at the beginning of the year, the Centre undertook important steps to realign programmes and operations to its strategic objectives. CTA is now placing a much stronger emphasis on creating partnerships with regional policy-making organisations, farmers’ groups and others working for the benefit of rural communities in ACP countries. The annual report highlights CTA’s work on climate change and agricultural extension, on markets and value chains, knowledge management and ICTs for development.